Asthma management practices in adults – findings from the German Health Update (GEDA) 2010 and the German National Health Interview and Examination Survey (DEGS1) 2008–2011. (2nd January 2016) - Steppuhn, Henriette; Langen, Ute; Mueters, Stephan; Dahm, Stefan; Knopf, Hildtraud; Keil, Thomas; Scheidt-Nave, Christa
Abstract: Objectives : In Germany, population-wide data on adherence to national asthma management guidelines are lacking, and performance measures (PM) for quality assurance in asthma care are systematically monitored for patients with German national asthma disease management program (DMP) enrollment only. We used national health survey data to assess variation in asthma care PM with respect to patient characteristics and care context, including DMP enrollment. Methods : Among adults 18–79 years with self-reported physician-diagnosed asthma in the past 12 months identified from a recent German National Health Interview Survey (GEDA 2010: N = 1096) and the German National Health interview and Examination Survey 2008–2011 (DEGS1: N = 333), variation in asthma care PM was analyzed using logistic regression analysis. Results : Overall, 38.4% (95% confidence interval: 32.5–44.6%) of adults with asthma were on current inhaled corticosteroid therapy. Regarding non-drug asthma management, low coverage was observed for inhaler technique monitoring (35.2%; 31.2–39.3%) and for provision of an asthma management plan (27.3%; 24.2–30.7%), particularly among those with low education. Specific PM were more complete among persons with than without asthma DMP enrollment (adjusted odds ratios ranging up to 10.19; 5.23–19.86), even if asthma patients were regularly followed in a different care context. Conclusions : Guideline adherence appears to be suboptimal, particularly with respect to PM related to patient counseling. Barriers to the translation of recommendations into practice need to be identified and continuous monitoring of asthma care PM at the population level needs to be established.